[Translated article] Medical Devices in Patients With Diabetes and Contact Dermatitis - J.P. Velasco-Amador; Á. Prados-Carmona; F.J. Navarro-Triviño (Elsevier, 2024)
The development and commercialization of glucose sensors and insulin pumps has revolutionized the management of diabetes. These devices have been linked to multiple cases of contact dermatitis in recent years, however, giving rise to a growing interest in identifying the sensitizing allergens. Isobornyl acrylate was clearly identified as one of the main allergens responsible for contact dermatitis among users of the FreeStyle glucose sensor and was subsequently removed from the product ingredients. Remarkably, however, it is still used in most other sensors on the market. The common adhesive ingredients colophony and abietic acid derivatives have also been shown to be sensitizing agents. New components under study, such as dipropylene glycol diacrylate, N,N-dimethylacrylamide, and triethylene glycol methacrylate have recently been identified as allergens, though they are not commercially available for clinical testing. The benefits offered by glucose sensors and insulin pumps may be offset by sensitization to product ingredients, in some cases forcing discontinuation and diminishing quality of life. Dermatologists should play a role in this clinical and research scenario, offering case-by-case guidance to endocrinologists on skin care and possible alternatives for patients with glucose sensors and insulin pumps who develop contact dermatitis. They should also collaborate with the manufacturers developing these devices. Resumen: El desarrollo y comercialización de los sensores de glucosa y las bombas de insulina han supuesto una revolución en el control de los pacientes diabéticos. En los últimos años se han detectado múltiples casos de dermatitis de contacto relacionados con estos dispositivos médicos, con el creciente interés sobre los alérgenos responsables de la sensibilización. Isobornil acrilato fue sin duda el alérgeno principal del dispositivo FreeStyle, motivando al fabricante a modificar la composición eliminando este alérgeno. Curiosamente, este alérgeno está presente en casi todos los sensores comercializados. La colofonia y derivados del ácido abiético desempeñan un papel relevante en cuanto al adhesivo. Recientemente aparecen nuevos componentes identificados como alérgenos, no comercializadas, como el dipropilene glicol diacrilato, la N,N-dimetilacrilamida, o el metacrilato de trietilenglicol, que están siendo foco de estudio. El impacto positivo que tiene el uso de estos dispositivos puede verse mermado por la sensibilización a uno de sus ingredientes, obligando en ocasiones a abandonar el dispositivo, y por ende, restando calidad de vida. El dermatólogo debe posicionarse respecto al estudio dirigido de estos pacientes, dando soporte a los servicios de endocrinología, con la finalidad de orientar tanto el cuidado de la piel como las alternativas posibles, especialmente con la colaboración de los fabricantes.